Temporal responses in sensorimotor cortex during hand movements - Sophia Gimple; Zachary V. Freudenburg; Nick F. Ramsey; Mariana P. Branco (PLoS ONE, 2026)
The role of primary somatosensory cortex (S1) in sensorimotor integration, classically limited to sensory processing, has recently been challenged. In particular, it is unclear whether neural signals in S1 activate prior to or after the primary motor cortex (M1) in the presence and absence of reafferent feedback. Here we aim to gain a better understanding of the temporal dynamics between S1 and M1, and the underlying neural processes involved in movement execution. We compare the onset latency of S1 and M1 signals in eight able-bodied participants implanted with high-density electrocorticography (ECoG) grids over the hand region of the sensorimotor cortex for both low- and high-frequency band (LFB and HFB) signals. Our results show a consistent activation of M1 electrodes before S1 electrodes across able-bodied participants for the HFB but no clear pattern for the LFB. Furthermore, we compared these results with two participants implanted with ECoG, who attempted movement with no or minimal reafference, showing similar effect in the HFB signals. These results call for an updated view of S1 beyond processing of sensory input, as they suggest S1 may also play a role during movement initiation. Better understanding of the integration of M1 and S1 signals will be undoubtedly critical for the understanding of neuromuscular disorders and the development of neurotechnology.